Provincial Climate Action Index and Its Use for Assessing Dual Carbon Policy of 31 Provinces in China - Jing Xu; Fengqiao Mei; Chuntian Lu; Bin Zhang; Min Wang (Asia & the Pacific Policy Studies)
ABSTRACT Dual carbon goals ushered in a new era of Chinaʼs climate policies. Provinces play a crucial role in translating climate goals into specific, detailed, and implementable policies, and they are key to Chinese commitments to carbon neutrality. We examine dual carbon policies at the provincial level to better understand the new landscape of local mitigation efforts in China. This research develops a Provincial Climate Action Index based on five policy categories: communication and knowledge sharing, planning guidance, mandatory regulations, funding, and governmental resources. We calculate the index scores of 31 Chinese provinces and identify 3 clusters: leaders, followers, and laggards in dual carbon policy, demonstrating both differences and similarities in provincial‐level actions to achieve climate goals. Provinces such as Shanghai, Beijing, and Anhui are pioneering, nearly half of provinces including Shandong and Shanxi, exhibit medium commitments to the goals, while 10 underperforming provinces such as Qinghai and Xizang lag behind.